Hurricane-induced lahars at Volcán de Colima (México): seismic characterization and numerical modeling - J. Ivonne Martínez-Valdés; Víctor Hugo Márquez-Ramírez; Velio Coviello; Lucia Capra (Revista Mexicana de Ciencias Geológicas)
The Volcán de Colima, one of the most active volcanoes in Mexico, has experienced several volcanic crises over the last century with the emplacement of voluminous block-and-ash flow deposits providing large volumes of loose material along the main ravines. During the rainy season, this material is easily eroded forming lahars. Over 40 events with variable magnitude (105-106 m3) have been detected each year. The largest events that cause damages to infrastructure are usually triggered during the hurricane season (from mid-August to October) when more than 250 mm of rain usually are accumulated over a few days. On 23 October 2015, Hurricane Patricia hit the Volcán de Colima. The hurricane was announced as having reached category 5 thereby representing the largest ever recorded hurricane event in Mexico. It rapidly weakened after landfall but followed a straight trajectory toward the volcano. Up to 400 mm of rain were recorded over 30 hours. The event was recorded at a monitoring station located in the middle reaches of the La Lumbre ravine on the SW flank of the volcano, which was equipped with a rain gauge, a geophone (10 Hz), and a video camera. A multi-pulse lahar started around 8 pm (GMT) and lasted for more than five hours. The seismic signal and the video images were analyzed to identify the timing of the main pulses, the sediment concentrations, and maximum flow peak discharge. Data show that the lahar was characterized by three main pulses, in the range of debris flows with maximum flow-depth of 8 m, interspersed by more dilute tails as hyperconcentrated flow, as also observed from the frequency contents of the seismic signal. A total volume of 2.5 × 106 m3 was estimated based on the strong correlation between the seismic amplitude and the flow discharge. The lahar destroyed one bridge and ~500 m of the interstate road leaving several villages cut off for a few days. Based on the flow magnitude, duration, and the associated damage, this event probably represents the largest one recorded over the last 20 years. The FLO-2D model was used to replicate the observed event to estimate the maximum inundation limits of lahars along the five principal ravines of the volcano, in an attempt to design a hazard map for catastrophic hurricane-induced events.